Code Alternations in Bilingual Representation and a Communication Strategy in Tuan Guru Bajangâ€™s Islamic Speech - Thohir, Lalu (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2017)
The present writing is a study of code alternation in TGBâ€™s Islamic speech. TGB which stands for â€œTuan Guru Bajangâ€ is a well-known name for Dr. M. Zainul Majdi, M.A, a famous Islamic preacher in Lombok and at present, he is the governor of West Nusa Tenggara province. The data of this study were obtained from one of TGBâ€™s Islamic speech recordings. They were first classified into inter-sentential switching, tag-switching, and intra-sentential switching and then they were analyzed to know their functions which involve a topic switch, effective and repetitive functions. The findings show that intra-sentential switching which reflects repetitive function appeared most frequently in TGBâ€™s Islamic speech. The code alternation in TGBâ€™s Islamic speech represents bilingualism and has proved to be an effective strategy in communication.